Expression of fibroblast growth factor 21 in patients with biliary atresia. (July 2016) - Li, Dawei; Lu, Tianfei; Shen, Conghuan; Liu, Yuan; Zhang, Jiang; Shan, Yuhua; Luo, Yi; Xi, Zhifeng; Qiu, Bijun; Chen, Qimin; Zhang, Jianjun; Xia, Qiang
Graphical abstract: Highlights: Serum FGF21 concentrations were significantly increased in BA patients as compared to healthy controls. Serum FGF21 levels were positively correlated with INR and bile acids and negatively correlated with serum albumin. The increased expression of FGF21 is partly dependent on FXR. Abstract: Fibroblast growth factor 21 is a critical circulating adipokine involving in metabolic disorders and various liver diseases. This study was performed to investigate whether FGF21 is also associated with the pathophysiology of biliary atresia. Serum FGF21 levels were measured in 57 BA patients and 20 age matched healthy controls. We also examined hepatic FGF21 mRNA expression and FGF21 protein levels in liver tissues obtained from 15 BA patients undergoing liver transplantation and 5 cases of pediatric donation after cardiac death donor without liver diseases by RT-PCR and Western blotting. Patients with BA showed significantly higher serum FGF21 levels than those without BA (554.7 pg/mL [83–2300] vs. 124.5 pg/mL [66–270], P < 0.05). Patients with BA also had significantly higher FGF21 mRNA and protein levels in hepatic tissues than control subjects. Serum FGF21 expression increased corresponding to the severity of liver fibrosis. Furthermore, serum FGF21 levels dropped significantly in BA patients within 6 months after liver transplantation and approached baseline in healthy controls (P > 0.05). In vivo, FXR knockout could significantly abrogate cholestasis induced FGF21 expression. FGF21 levels in serum and liver tissue increased significantly in BA patients. In vivo, cholestasis could induce FGF21 expression in FXR dependent manner.